Greece : 2021 Article IV Consultation-Press Release; and Staff Report. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Greece entered the pandemic with an unfinished recovery, but the country has demonstrated resilience in facing COVID-19. The economy contracted by 8.2 percent in 2020, better than expected given Greece's high dependence on tourism and pre-existing vulnerabilities. The government provided among the largest on-budget fiscal stimuli in the euro zone and supervisory and ECB accommodation shielded the banking sector and kept financing conditions highly accommodative. Despite the pandemic, reforms progressed in a number of areas, albeit at a slower pace than in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Greece